The impact of physical components of the environment on the sociability of cultural-recreational spaces case study: Rasht cultural complex. Issue 1 (31st December 2022) - Hashemi, Nima; Emami, Farnaz; Abdshahzadeh, Parinaz; Niaei, Ali Asghar
ABSTRACT: The focus of the research is to analyze and evaluate the impact of physical space in the environment as a spatial system on the social interactions of users. The role of the physical components of the environment for the sociability of the environment and the desire to work in spaces is examined. In this research, the physical components of the environment as an independent variable that affect the quality of socialization of physical spaces as a dependent variable. To analyze, the physical environment is considered a socio-behavioral place. In this regard, by recognizing the types of public spaces as a physical environment and recognizing their qualities and functions, we reach the necessity of having cultural-recreational spaces as a platform for the formation of social life. The present research descriptively and analytically examines the sociability of the physical environment as a necessary spatial quality in cultural-recreational spaces, and by recognizing the physical components and sociability activity, analyzes these components in the present case. Data collection was done through questionnaires, interviews, and field observations. The final part of this research shows that security, as the most important environmental quality that results from the impact of components such as confinement and lighting and control and monitoring and visual access, has a direct impact on the sociability of the analyzed sample.